Fourier Series and the Zeta Function
Date: 08/13/98 at 17:58:42 From: Patrick Perry Subject: Evaluating the Riemann-Zeta Function Dr. Math: I was reading about the Zeta function in a complex analysis book, and I have seen the functional equation relating the Gamma function to the Zeta function. However, it is still not clear to me how to evaluate something like "zeta of 2." Could you please give me some idea of how it's done?
Date: 08/13/98 at 18:52:37 From: Doctor Anthony Subject: Re: Evaluating the Riemann-Zeta Function Patrick: Z(2) is the series shown below: 1 + 1/2^2 + 1/3^2 + 1/4^2 + 1/5^2 + . . . . . = pi^2/6 This can be proved by advanced trigonometric manipulations, but a more elegant method is with the aid of Fourier series. A brief note on Fourier series is necessary if you are to understand the method. For a great many functions within the range -pi < x < pi we can express f(x) as an infinite series of the form: f(x) = a(0)/2 + SUM(n=1 to inf.)[a(n)cos(nx) + b(n)sin(nx)] where the a(i), b(i) are constants. So: f(x) = a(0)/2 + a(1)cos(x) + a(2)cos(2x) + a(3)cos(3x) + .... + b(1)sin(x) + b(2)sin(2x) + b(3)sin(3x) + .... This series is periodic with period 2pi and the convention is to take the interval -pi < x < pi. The way to evaluate the constants a(i) is to multiply both sides by cos(nx) and then integrate between -pi and pi. INT(-pi to pi)[f(x)cos(nx)dx] = pi a(n) (proof given below) So a(n) = (1/pi)INT(-pi to pi)[f(x)cos(nx)dx] Similarly: b(n) = (1/pi)INT(-pi to pi)[f(x)sin(nx)dx] Also note: a(0) = (1/pi)INT(-pi to pi)[f(x) dx] Proof of above results. ---------------------- INT(-pi to pi)[cos(mx)cos(nx)dx] m not equal n = (1/2)INT[cos(m+n)x + cos(m-n)x]dx between -pi and pi = 0 since sin(any multiple of pi) = 0 but: INT(-pi to pi)[cos^2(nx)]dx = pi So all the terms cos(mx)cos(nx) (m not equal to n) disappear and we get only the term in cos^2(nx) This gives the result: INT[f(x)cos(nx)dx] = a(n) pi and so: a(n) = (1/pi)INT[f(x) cos(nx) dx] In the case n = 0 we get: INT[f(x) dx] = INT[a(0)/2 dx] + 0 + 0 + ... = a(0) pi So: a(0) = (1/pi)INT[f(x) dx] Similarly: b(n) = (1/pi)INT[f(x)sin(nx)dx] since all terms in sin(mx)sin(nx) (m not equal to n) disappear leaving only the term in sin^2(nx). Also all terms in sin(mx)cos(nx), whether or not m = n disappear on integration between -pi and pi. This means that we can evaluate all the a(i), b(i) and express f(x) as an infinite series in sines and cosines of multiples of x. There are a great many functions that can be expressed in this way in the interval -pi to pi. We can now turn our attention to finding the sum of the series: 1 + 1/2^2 + 1/3^2 + 1/4^2 + .... Let f(x) = x^2. This is an even function of x so we know that none of the sine terms of the Fourier series can be present. We need only look at the a(i) terms. For all a(n) we get: pi a(n) = INT(-pi to pi)[x^2 cos(nx)dx] When n = 0 this gives a(0) = (2/3)pi^2. When n is greater than 0, integration by parts in 3 steps gives: a(n) = 4(-1)^n/n^2 The Fourier series is pi^2/3 + 4 SUM(1 to infinity)(-1)^n/n^2 cos(nx) With x = pi, we get: pi^2 = pi^2/3 + 4 SUM(-1)^n/n^2 cos(n pi) and since cos(n pi)= (-1)^n, this produces +'s for each term: 2 pi^2/3 = 4 SUM[1 + 1/2^2 + 1/3^2 + ..... to infinity] pi^2/6 = 1 + 1/2^2 + 1/3^2 + 1/4^2 + ..... to infinity - Doctor Anthony, The Math Forum Check out our web site! http://mathforum.org/dr.math/
Search the Dr. Math Library:
Ask Dr. MathTM
© 1994- The Math Forum at NCTM. All rights reserved.